Three‐dimensional Martian ionosphere model: I. The photochemical ionosphere below 180 km. Issue 10 (8th October 2013) - González‐Galindo, F.; Chaufray, J.‐Y.; López‐Valverde, M. A.; Gilli, G.; Forget, F.; Leblanc, F.; Modolo, R.; Hess, S.; Yagi, M.
<x xml:space="preserve">Abstract</x> [1] We describe the Mars ionosphere with unprecedented detail in 3‐D, as simulated by a Mars general circulation model (the Laboratoire de Météorologie Dynamique Mars GCM), and compare it with recent measurements. The model includes a number of recent extensions and improvements. Different simulations for a full Martian year have been performed. The electron density at the main ionospheric peak is shown to vary with the Sun‐Mars distance and with the solar variability, both in the long‐term (11 year solar cycle) and on shorter temporal scales (solar rotation). The main electronic peak is shown to be located at the same pressure level during all the Martian year. As a consequence, its altitude varies with latitude, local time, and season according to the natural expansions and fluctuations of the neutral atmosphere, in agreement with previous models. The model predicts a nighttime ionosphere due only to photochemistry. The simulated ionosphere close to the evening terminator is in agreement with observations. No effort has been made to explain the patchy ionosphere observed in the deep nightside. We have compared the modeled ionosphere with Mars Global Surveyor and Mars Advanced Radar for Subsurface and Ionosphere Sounding data. The model reproduces the solar zenith angle variability of the electron density and the altitude of the peak, although it underestimates the electron density at the main peak by about 20%. The electron density at the secondary peak is strongly underestimated by the model, probably due to a very crude representation of the X‐ray solar flux. This is one of the aspects that needs a revision in future versions of the model.